Development of a test equipment for pesticide protective fabric evaluation and studies on simple cotton woven fabrics. (April 2014) - Abirami, Ramanan; Selvakumar, N
In this study, efforts were taken to identify the most suitable cotton fabric with commonly used structure to be used as protective fabric by the pesticide applicators in the tropical regions, specifically at the time of spraying in the field. As the situation demanded the generation and use of pesticide-borne air for the evaluation of cotton fabrics considered in the study, a test equipment with appropriate features was developed and used. The study revealed that twill fabrics of medium weight construction provide better protection than plain fabrics, especially when they are produced with coarser yarns to achieve the required fabric weight. They are found to give enhanced protection when they are subjected to raising operation. Fabric raised on both the sides performs better than the face side raised fabric. On the contrary, these fabrics in raised or unraised state are found to slightly go down in their performance when they are wet and their performance decreases with increase in wetness. Hence, it is suggested that use of raised fabrics may be avoided for the preparation of pesticide protective clothing as the pesticide applicators are bound to sweat at the time of spraying. As the unraised fabrics give comparatively lower performance reduction on wetting, it can be recommended for the pesticide applicators with the instruction to change the clothing when it become wet to ensure protection.